Multisensory Experiences: A Primer - Velasco, Carlos; Obrist, Marianna (Frontiers in Computer Science, 2021)
We present a primer on multisensory experiences, the different components of this concept, as well as a reflection of its implications for individuals and society. We define multisensory experiences, we illustrate how to understand them, we elaborate on the role of technology in such experiences, and present the three laws of multisensory experiences, which we can guide discussion on their implications. Further, we introduce the case of multisensory experiences in the context of eating and human-food interaction to illustrate how its components operationalize. We expect that this article provides a first point of contact for those interested in multisensory experiences, as well as multisensory experiences in the context of human-food interaction.